Creative Procedure of Bin Products for Children - Songwut Egwutvongsa; Somchai Setvisat (My University, 2021)
This research had the objective to design children’s bins and make a comparison of the new and old bin patterns. The group sampling consisted of 652 participants composed of the students and personnel in a school in Khlong Kum District, Bangkok, Thailand. For this case, multistage random sampling was used with 234 participants, and the research tools were composed of five-point Likert scale questionnaires that were measured with Cronbach’s alpha coefficient with a level of 0.91, independent t-test and multiple regression analysis. From the above information, it was found that the influencing factors to the children’s bin’s design involved the beauty (0.32), specific attributes, (0.24), morale (0.16), ergonomics (0.10), safety (0.07), application (0.07), and the materials (0.05). In addition, when testing the model, it was found that the new bin product patterns had the most satisfaction level ( =4.55; S.D.=0.30), followed by the original bin product patterns that had a moderate satisfaction level ( =3.08; S.D.=0.52). Finally, when comparing the differences of the satisfaction level by using the t-test statistics, it was found that the children’s satisfaction to the new bin patterns were at a higher level than the original ones with a statistical significance level of .05. Received: 3 July 2021 / Accepted: 16 August 2021 / Published: 5 September 2021
Keywords: Digital Media and Visual Art